2021
DOI: 10.5430/ijfr.v12n4p135
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Measurement of Indian Banking Industry: An Empirical Comparative Analysis

Abstract: The following study is conducted to measure and compare the performance of 32 Indian banks, 21 public banks, and 11 private banks, at two tiers during the period of 2008–2018. Industrial analysis of both the public and private banking sectors is conducted in the first tier, followed by an individual bank-level analysis at the second tier. Data analysis consists of deposits, assets, and equity as inputs to measure the outputs practicing data envelopment analysis techniques. The empirical results portray a mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Shabbir and Zeb's (2020) study also revealed that bank types affect customers' trust differently. According to Ahmad and Khan (2021), the technical efficiency of private banks has an edge over public banks. In contrast, Kaura's (2013) study showed no significant difference between public and private banks relating to the positive IT impact on customer satisfaction.…”
Section: Bank Revenue and Bank Codementioning
confidence: 99%
“…Shabbir and Zeb's (2020) study also revealed that bank types affect customers' trust differently. According to Ahmad and Khan (2021), the technical efficiency of private banks has an edge over public banks. In contrast, Kaura's (2013) study showed no significant difference between public and private banks relating to the positive IT impact on customer satisfaction.…”
Section: Bank Revenue and Bank Codementioning
confidence: 99%